Comparative Analysis of Emotional and Psychological Degree Expression Between Chinese and Thai Taking “得”and “/tɕon/” Sentences as an Example: 汉泰情感心理程度表达对比—以“得”、“ จน(/tɕon/)”为例 - Woraditnitiwaraatorn, Nawanan (Published by Confucius Institute UNS, 2024)
Each language has its own unique characteristics of degree expression. Whether expressing positive or negative feelings, these can be conveyed through language. Words involving emotional categories such as joy, anger, sorrow, and fear are particularly embodied in emotional-psychological verbs and emotional-psychological adjectives. This paper aims to investigate the expression of emotional-psychological degree in Chinese and Thai, focusing on the use of 'de' in Chinese and 'จน' (/ton/) in Thai as auxiliary markers in sentences. The study finds that the characteristics of emotional-psychological degree in both languages cover four aspects: first, the concrete and abstract expression of abnormal degree; second, the degree expression of metaphor; third, the degree expression of specific behavior; and fourth, the degree expression of extreme emotions. Thai is more inclined to use specific actions and metaphors, while Chinese primarily uses extreme emotions and metaphors. The common points of degree expression in the two languages revolve around the content of abnormal expressions.